LiBSi2: A Tetrahedral Semiconductor Framework from Boron and Silicon Atoms Bearing Lithium Atoms in the Channels1. Issue 23 (22nd April 2013) - Zeilinger, Michael; van Wüllen, Leo; Benson, Daryn; Kranak, Verina F.; Konar, Sumit; Fässler, Thomas F.; Häussermann, Ulrich
<x xml:space="preserve">Abstract</x> Silicon swallows up boron: The novel open tetrahedral framework structure (OTF) of the Zintl phase LiBSi2 was made by applying high pressure to a mixture of LiB and elemental silicon. The compound represents a new topology in the B‐Si net (called tum), which hosts Li atoms in the channels (see picture). LiBSi2 is the first example where B and Si atoms form an ordered common framework structure with B engaged exclusively in heteronuclear BSi contacts.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>